Total Synthesis of Natural Disaccharide Sambubiose - Simone Lucarini; Maria Gessica Ciulla; Paola Mestichelli; Andrea Duranti (MDPI AG, 2020)
A practical and robust synthetic method to obtain the natural disaccharide sambubiose (2-O-β-D-xylopyranosyl-D-glucopyranose) is reported, exploring the key step in the synthesis, i.e., stereoselective O-glycosylation. Specifically, the best combinations of glycoside donors and acceptors were identified, stereospecific control of the reaction was achieved by screening several catalysts and protection/deprotection steps were evaluated and improved. The best result was obtained by coupling allyl 3,5,6-tri-O-benzyl-β-D-glucofuranoside with 2,3,4-tri-O-acetyl-D-xylopiranosyl-α-trichloro acetimidate in the presence of trimethylsilyl triflate as a catalyst giving the corresponding protected target compound as a correct single isomer. The latter was transformed accordingly into the desired final product by deprotection steps (deallylation, deacetylation, and debenzylation). Sambubiose was synthesized into a satisfactory and higher overall yield than previously reported and was also characterized.